Functional analysis of germline RAD51C missense variants highlight the role of RAD51C in replication fork protection. Issue 8 (23rd December 2022) - Kolinjivadi, Arun Mouli; Chong, Siao Ting; Choudhary, Ramveer; Sankar, Haresh; Chew, Ee Ling; Yeo, Claresta; Chan, Sock Hoai; Ngeow, Joanne
Abstract: Monoallelic or biallelic RAD51C germline mutations results in chromosome instability disorders such as Fanconi anemia and cancers. The bona fide function of RAD51C is to assist RAD51 nucleoprotein filament onto single-strand DNA to complete homologous recombination (HR) repair. In addition to HR repair, the role of RAD51C in DNA replication is emerging when replication forks are transiently or irreversibly stalled. We identified novel RAD51C variants of uncertain significance (VUS) from breast, ovarian, pancreatic and gastric cancer patients and functionally characterized the effect of these variants in replication fork protection and double-strand breaks (DSB's) repair. In RAD51C-deficient Chinese hamster CL-V4B cells, expression of RAD51C F164S, A87E, L134S and E49K variants heightened sensitivity to mitomycin C (MMC), etoposide and PARP inhibition. Differently, expression of subset of RAD51C variants R24L, R24W and R212H displayed mild sensitivity to MMC, etoposide and PARP inhibition. Further functional characterization of a subset of variants revealed that Rad51C F164S, A87E, L134S and E49K variants displayed reduced RAD51 foci formation and increased overall nuclear single strand DNA levels in the presence of replication stress. Additionally, DNA fiber assay revealed that RAD51C F164S, A87E, L134S and E49K variants displayed defective replication fork protection upon prolonged fork stalling. Investigations using patient-derived lymphoblastoid cell line carrying heterozygous RAD51C L134S variant showed an impairment in RAD51 chromatin association and replication fork protection, suggestive of deleteriousness of this VUS variant. Overall, our findings provide more insights into molecular roles of RAD51C in replication fork integrity maintenance and in DSB repair.